A Bodily Code Analysis Used in Revealing an Imaginary Friend Character in Bill Watterson's Comic Strip Calvin and Hobbes - Setiawan, Dimas (2013)
Studi berjudul "A Bodily Codes Analysis Used in Revealing an Imaginary Friend Character in Bill Watterson's Comic Strip Calvin and Hobbes" mencoba untuk mencari representasi dari karakter khayal bernama Hobbes berdasarkan gerak-geriknya (bodily code) yang tampak pada 15 komik strip yang telah dipilih dengan sengaja.. Untuk memperoleh pemahaman yang mendalam, studi ini mempergunakan empat basic premises of experientialism yang dikemukakan oleh Buckland (2004) terhadap 9 jenis gerak-gerik yang dikemukakan oleh Chandler (2002). Studi ini menggunakan metode kwalitaif dalam hal pendeskripsian premises dalam narasi. Studi ini menemukan bahwa Hobbes membuat 52 tampilan sebagai harimau sungguhan (15.71%), 52 gerak tubuh (15.71%), 50 sikap tubuh (15.11%), 47 kedekatan (14.20%), 43 orientasi fisik (12.99%), 42 ekspresi wajah (12.69%), 38 tatapan (11.48%), 7 kontak tubuh (2.11%), and 0 anggukan (0%). Selanjutnya, studi ini juga menemukan 5 representasi karakter Hobbes. Pertama, Hobbes merupakan gambaran dari Calvin. Representasi kedua adalah Hobbes sebagai teman dari Calvin. Ketiga, Hobbes direpresentasikan sebagai hewan peliharaan. Representasi keempat adalah Hobbes sebagai lawan dari Calvin. Terakhir, Hobbes direpresentasikan sebagai harimau yang memiliki naluri hewan liar. Oleh karena itu, di dalam komik strip Bill Watterson, Calvin and Hobbes, Hobbes dibayangkan sebagai sesuatu yang terdekat hingga terjauh dari Calvin. Keyword: Bodily Codes, Basic Premises of Experientialism, Representasi, Komik Strip. The study entitled "A Bodily Codes Analysis Used in Revealing an Imaginary Friend Character in Bill Watterson's Comic Strip Calvin and Hobbes" seeks to discover the representation of imaginary character of Hobbes based on his bodily codes occurred in the 15 selected strips purposively. To obtain deeper understanding, this study applies four basic premises of experientialism proposed by Buckland (2004) towards 9 bodily codes proposed by Chandler (2002). This study uses a qualitative method in order to describe the premises in a narrative way. This study discovered that Hobbes makes 52 appearances as a real tiger (15.71%), 52 gestures (15.71%), 50 postures (15.11%), 47 proximities (14.20%), 43 physical orientations (12.99%), 42 facial expressions (12.69%), 38 gazes (11.48%), 7 bodily contacts (2.11%), and 0 head-nods (0%). Furthermore, this study also discovered 5 representations of Hobbes. The first is Hobbes as a reflection of Calvin. The second representation is Hobbes as a friend of Calvin. Third, Hobbes is represented as a pet. The forth representation is Hobbes as an opponent of Calvin. Lastly, Hobbes is represented as a real tiger which has instincts as a wild animal. Therefore, in Bill Watterson's Calvin and Hobbes, Hobbes is visualized as something very close to very distant for Calvin. Keyword: Bodily Codes, Basic Premises of Experientialism, Representation, Comic Strip.